Reservoir Characterization around Geothermal Field, West Java, Indonesia Derived from 4-D Seismic Tomography. (January 2016) - Ry, Rexha Verdhora; Nugraha, A D
Abstract: Observation of micro-seismic events induced by intensive geothermal exploitation in a particular geothermal field, located in West Java region, Indonesia was used to detect the fracture and permeability zone. Using local monitoring seismometer network, tomographic inversions were conducted for the three-dimensional Vp, Vs, and Vp/Vs structure of the reservoir for January - December 2007, January - December 2008, and January - December 2009. First, hypocenters location was relocated using joint hypocenter determination (JHD) method in purpose to estimate best location. Then, seismic tomographic inversions were conducted using delay time tomography for dataset of every year respectively. The travel times passing through the three-dimensional velocity model were calculated using ray tracing pseudo-bending method. Norm and gradient damping were added to constrain blocks without ray and to produce smooth solution model. The inversion algorithm was developed in Matlab environment. Our tomographic inversion results from 3-years of observations indicate the presence of low Vp, low Vs, and low Vp/Vs ratio at depths of about 1 - 3 km below sea level. These features were interpreted may be related to steam-saturated rock in the reservoir area of this geothermal field. The locations of the reservoir area were supported by the data of well- trajectory, where the zones of high Vp/Vs were observed around the injection wells and the zones of low Vp/Vs were observed around the production wells. The extensive low Vp/Vs anomaly that occupies the reservoir is getting stronger during the 3-years study period. This is probably attributed to depletion of pore liquid water in the reservoir and replacement with steam. Continuous monitoring of Vp, Vs, and Vp/Vs is an effective tool for geothermal reservoir characterization and depletion monitoring and can potentially provide information in parts of the reservoir which have not been drilled.